Implications of Climate Change on Nature-Based Tourism Demand: A Segmentation Analysis of Glacier Site Visitors in Southeast Iceland - Johannes Welling; Þorvarður Árnason; Rannveig Ólafsdóttir (Sustainability, 2020)
Since the end of the 20th century, glaciers are shrinking at an accelerated pace worldwide. This fuels the concern that increased glacier recession will lead to changes in the accessibility, safety, and amenity of many popular glacier tourist destinations—which may, in turn, affect the number of tourists visiting these areas. However, tourist responses to climate-induced environmental changes are still not well understood. Therefore, this study assesses the effects of the implications of glacier recession for glacier site visitation demand and examines the heterogeneity of tourists’ responses to these implications for visitation, combining a contingent behavior approach with multivariate cluster analysis. Data were generated from a quantitative survey of 565 visitors to Vatnajökull National Park in southeast Iceland. The results show that climate change induced environmental changes greatly affect nature-based tourism demand, and that the responses of glacier visitors to those changes vary considerably across visitation implications and visitor segments. In order to facilitate future glacier site visitation demand in a sustainable manner, decision-makers and practitioners need to act more proactively and incorporate visitor segment differences into their planning, education, communication efforts and product development.